Design, Synthesis, and Biochemical Evaluation of Alpha‐Amanitin Derivatives Containing Analogs of the trans‐Hydroxyproline Residue for Potential Use in Antibody‐Drug Conjugates. Issue 40 (18th June 2021) - Matinkhoo, Kaveh; Wong, Antonio A. W. L.; Hambira, Chido M.; Kato, Brandon; Wei, Charlie; Müller, Christoph; Hechler, Torsten; Braun, Alexandra; Gallo, Francesca; Pahl, Andreas; Perrin, David M.
Abstract: Alpha‐amanitin, an extremely toxic bicyclic octapeptide extracted from the death‐cap mushroom, Amanita phalloides, is a highly selective allosteric inhibitor of RNA polymerase II. Following on growing interest in using this toxin as a payload in antibody‐drug conjugates, herein we report the synthesis and biochemical evaluation of several new derivatives of this toxin to probe the role of the trans ‐hydroxyproline (Hyp), which is known to be critical for toxicity. This structure activity relationship (SAR) study represents the first of its kind to use various Hyp‐analogs to alter the conformational and H‐bonding properties of Hyp in amanitin. Abstract : Getting at the Hyp of amanitin : A formal study of structure‐function relationships for trans ‐hydroxyproline – a key functionality the specifies the toxicity of amanitin is undertaken to probe aspects of H‐bonding and other interactions with analogs of hydroxyl‐proline. The toxin is surprisingly refractory to replacing the hydroxyproline.